Casebook on Insurgency and Revolutionary Warfare - Tompkins Jr, Paul J.; United States Army Special Operations Command (Public Intelligence, 2012)
Unconventional Warfare is the core mission and organizing principle for US Army Special Forces. The Army is the only military organization specifically trained and organized to wage Unconventional Warfare. From their inception, Special Forces and Army Special Operations Forces were largely focused on developing regional, cultural, and language skills in recognition of the singular importance of the human dimensions of war among the people. We have consistently recognized the importance of dedicating intellectual efforts to better understand the nature of our environment, the motivations and behavior of our enemies. Investment in our human capital is an essential part of developing and maintaining sufficient capability to conduct Unconventional Warfare or Unconventional Warfare-related operations in sensitive environments or conditions.
Keywords: Rebeliones; Rebeliones; Guerra